Podatek dochodowy od osób fi zycznych: progresywny czy proporcjonalny? - Podstawka, Marian; Deresz, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The current system of income tax on individuals was created in the period 1991–1994. At that time it was considered to be a modern and coherent system that met economic needs. However, numerous changes arising as a result of budgetary needs meant that the system became unduly complex and unmanageable. The introduction of a single flat rate tax in Poland is very controversial. It has divided opinion, especially that of economists, politicians and society as a whole. Both sides of the argument point out the advantages and disadvantages of applying one tax rate regardless of total income of individuals. The aim of this article is to highlight these issues in economic and social terms as well as discussing how the organization and administration of the tax system can be streamlined. The study consists of an introduction and four parts. In the first one, the main concept of taxes is presented. The second one is devoted to tax justice and the third part to tax refunds which are one of the elements of the tax system. The last part outlines the main problems connected with, and the influence of social inequality on economic growth.